2004
DOI: 10.1016/j.beproc.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Economic context and pigeons’ risk-taking: an integrative approach

Abstract: The present work tested pigeons' (Columba livia) risk sensitivity to changes in resource availability in the concurrent-chains choice procedure. Subjects were provided choices, generally between variable-ratio (VR) and fixed-ratio (FR) outcome schedules with equal or different mean values. Predictions from ecology's risk sensitivity, behavioral economic's rate maximization, and psychology's delay-reduction theory were contrasted under settings where budget was adversely affected by one of three manipulations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
(54 reference statements)
1
9
1
Order By: Relevance
“…Participants in the VI30sMean50 condition preferred the mixed alternative to a significantly greater extent than those in the FI1sMean50 condition. This result stands in contrast to findings which showed that when you increase initial-link delay in a concurrent-chains schedule, preference for the shorter terminal link decreases (Goldshmidt & Fantino, 2004). However, the same experiment showed that preference for the variable schedule increased as mean terminal-link values increased; a finding which is consistent with the results from the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Participants in the VI30sMean50 condition preferred the mixed alternative to a significantly greater extent than those in the FI1sMean50 condition. This result stands in contrast to findings which showed that when you increase initial-link delay in a concurrent-chains schedule, preference for the shorter terminal link decreases (Goldshmidt & Fantino, 2004). However, the same experiment showed that preference for the variable schedule increased as mean terminal-link values increased; a finding which is consistent with the results from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…For conditions where the initial link was VI 30s, a monotonic increase in preference was observed for the mixed option across conditions (Figure 2). This result is in agreement with nonhuman studies which found that preference for variability increased as terminal-link schedule values increased (McSweeney, Kowal, & Murphy, 2003; Goldshmidt & Fantino, 2004). …”
Section: Discussionsupporting
confidence: 92%
“…In biology, the concept of risk-sensitivity has previously been mainly applied to foraging, feeding, and reproduction (Houston, 1991; Hurly and Oseen, 1999; Shafir et al, 1999; Kirshenbaum et al, 2000; Shapiro, 2000; Bateson, 2002; Goldshmidt and Fantino, 2004; Heilbronner et al, 2008; Matsushima et al, 2008; Wong et al, 2009; Bardsen et al, 2010; Kawamori and Matsushima, 2010). There have also been investigations on the neural substrate of risk-sensitivity in economic decision tasks in which macaque monkeys “gambled” for fluid rewards (McCoy and Platt, 2005; Hayden et al, 2008; Long et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…al., 1995) that economic context would generally have no effect on choice seemed counter-intuitive. Thus, Goldshmidt and Fantino (2004) conducted a series of experiments on this question with pigeons and Orduna and Bouzas (2004) reported a study on the effects of energy budget on risky choice in both pigeons and doves. In this section we summarize the main results of these studies.…”
Section: Economic Context and Risky Choice In Pigeons And Dovesmentioning
confidence: 99%
“…Whereas Goldshmidt and Fantino (2004) utilized the concurrent-chains procedure, Orduna and Bouzas (2004) made use of the successive-encounters procedure developed by Lea (1979) to study behavior simulating foraging in pigeons. Their results also permitted a test between the risk-sensitivity view and DRT.…”
Section: Economic Context and Risky Choice In Pigeons And Dovesmentioning
confidence: 99%